Synthesis of Hollow Co–Fe Prussian Blue Analogue Cubes by using Silica Spheres as a Sacrificial Template. Issue 8 (7th August 2018) - Azhar, Alowasheeir; Zakaria, Mohamed B.; Ebeid, El‐Zeiny M.; Chikyow, Toyohiro; Bando, Yoshio; Alshehri, Abdulmohsen Ali; Alghamdi, Yousef Gamaan; Cai, Ze‐Xing; Kumar, Nanjundan Ashok; Lin, Jianjian; Kim, Hansu; Yamauchi, Yusuke
Abstract: Herein, we report a novel method for the formation of hollow Prussian blue analogue (CoFe–PBA) nanocubes, using spherical silica particles as sacrificial templates. In the first step, silica cores are coated by a CoFe–PBA shell and then removed by etching with hydrofluoric acid (HF). The cubic shape of CoFe–PBA is well‐retained even after the removal of the silica cores, resulting in the formation of hollow CoFe–PBA cubes. The specific capacity of the hollow CoFe–PBA nanocubes electrodes is about two times higher than that of solid CoFe–PBA nanocubes as storage materials for sodium ions. Such an improvement in the electrochemical properties can be attributed to their hollow internal nanostructure. The hollow architecture can offer a larger interfacial area between the electrolyte and the electrode, leading to an improvement in the electrochemical activity. This strategy can be applied to develop PBAs with hollow interiors for a wide range of applications. Abstract : Interior design : A method for the formation of hollow Prussian blue analogue (CoFe–PBA) nanocubes is reported, using spherical silica particles as sacrificial templates. A hollow architecture can offer a larger interfacial area between the electrolyte and the electrode, leading to an improvement in the electrochemical activity. This strategy could be applied to develop more PBAs with hollow interiors for a wide range of applications.